Recovery Strategy for Micro, Small and Medium Enterprises in the Creative Economy Sector During the COVID-19 Pandemic: A Case Study of Sengkang Silk - Syukriah Mathory, Eljihad Akbari; Murtafia, Murtafia; Rahmat, Rahmat; Sayuti, Nuraeni (KnE Social Sciences, 2022)
Micro, small and medium enterprises (MSMEs), especially in the creative economy sector in Wajo Regency, have been impacted by the COVID-19 pandemic that has lasted for over a year. This study aimed to examine how MSME actors can create a new market space while maintaining valuable buyers and being able to determine prices that can compete with others. Based on this, the research team attempted to uncover a model of an MSME-led recovery strategy for the creative economy sector during the COVID-19 pandemic, with a focus on woven fabrics. The researchers analyzed the strengths and weaknesses of the industry and the opportunities and threats. Descriptive qualitative methods were used. The recovery strategy was evaluated using the five-carrier analysis method and SWOT analysis. According to the Porter’s Five Forces Analysis, the COVID-19 pandemic did not fundamentally impact the entire silk fabric industry in Sengkang, but it did impact people buying the product. In addition, the results showed that artisans aggressively promoted silk fabrics with an emphasis on a market size strategy. The strategic direction provided a competitive advantage to the Sengkang silk industry, especially in the different promotions in the market space. Keywords: recovery strategy, MSMEs, Sengkang silk industry, creative economic